Parallel Electrical Conductivity in the Topside Ionosphere Derived From Swarm Measurements. Issue 2 (27th January 2021) - Giannattasio, F.; De Michelis, P.; Pignalberi, A.; Coco, I.; Consolini, G.; Pezzopane, M.; Tozzi, R.
Abstract: Our knowledge of the physical properties of the topside ionosphere is still incomplete. A key point still not fully understood is how field‐aligned currents are generated, evolve and dissipate in the ionosphere. Answering to this question is fundamental for a better understanding of the mechanisms regulating the coupling between magnetosphere and ionosphere and to shed light on the physical processes inherent to space weather events occurring in the Earth's ionosphere. In this framework a relevant role is played by the ionospheric conductivity. The purpose of this study is to analyze the main properties of the electrical conductivity parallel to the geomagnetic field from a climatological point of view. The statistical study of the electrical conductivity is proposed using four years of in‐situ electron density and temperature measurements at 1 Hz acquired by the European Space Agency's Swarm A satellite. Variations due to seasonal effects are also investigated. Finally, starting from observations and comparing our results with those obtained using International Reference Ionosphere model, we give a first estimation of the conductivity mainly due to particle precipitation. Key Points: We studied the parallel electrical conductivity in the topside ionosphere at high magnetic latitudes by using 4‐year measurements acquired by the Swarm mission We investigated both the climatological properties and the seasonal variations of electrical conductivity By comparing the results obtained with the International Reference Ionosphere model we estimated the contribution to electrical conductivity mainly due to particle precipitation